Transmission line sag and magnetic field analysis with sag parabolic equations and Biot-Savart law - Ahsan, Matiullah; Baharom, Md Nor Ramdon; Zainal, Zainab; Hassan, Omar Abu; Hanim, Faridah; Kamarudin, Saufi; Abd Rahman, Rahisham; Yousof, Mohd Fairouz Mohd; Jamail, Nor Akmal Mohd; Othman, Nordiana Azlin (Institute of Advanced Engineering and Science, 2025)
This study presents a novel approach to enhance the precision of calculating sag and magnetic fields beneath overhead transmission lines. The Biot-Savart law is integrated with parabolic equations to assign multiple magnetic field sources to each conductor, resulting in improved prediction accuracy. Addressing oversimplifications in traditional models improves the analysis of transmission lines in real-world scenarios. An analysis was performed using MATLAB and Simulink to validate the effectiveness and broad applicability of different configurations. The results demonstrated a significant improvement in precision compared to traditional methods, indicating that this approach has the potential to establish new benchmarks in the field. This methodology makes significant contributions to electromagnetic studies, offering engineers a reliable tool for designing transmission systems that are both safer and more efficient. This advancement in electrical engineering greatly improves transmission network performance by enhancing sag and magnetic field prediction accuracy. This aids in better maintenance planning and reduces outage risks, resulting in more efficient operations and improved overall performance.